Simulation and experimental analysis of a suspension system - Ab Ghani, Mohd. Satar (2006)
This research was carried out to investigate the response characteristics of a two-degree of freedom (DOF) suspension system with the proposed active force control (AFC) as the main control element. Both simulation and experimental studies were carried out for this purpose. In the simulation study, three types of control methods were examined and compared involving the classic proportional –integral – derivative (PID) controller , PID-AFC with crude approximation (CA) and also PIDAFC with embedded iterative learning method (ILM). The potential of the AFC schemes as robust systems were particularly highlighted. A number of loading conditions including appropriate road disturbance, and external disturbance are modelled and applied to the proposed systems to test for the system robustness. The results of the simulation study show that active suspension system using AFC with crude approximation (CA) control show its superiority in terms of better responses of the body mass displacement and acceleration, and suspension deflection compared with other methods considered in the study. Result of frequency analysis also shows that active systems are more stable compared with the passive system. In the experimental study, a working model of the suspension test rig was fully developed to test for the system performance. The laboratory scaled physical rig was developed using the MATLAB/ S imulink w ith Real T ime Workshop (RTW) tool that have been interfaced with suitable data acquisition card via a personal computer (PC) as the main controller. The results of the experimental study clearly indicate the superiority of the proposed PID-AFC scheme as a robus t active suspension control compared to the other schemes considered in the study.